Thinking with Diplomacy: Within and Beyond Practice Theory. Issue 4 (18th October 2021) - Constantinou, Costas M; Dittmer, Jason; Kuus, Merje; McConnell, Fiona; Opondo, Sam Okoth; Pouliot, Vincent
Abstract: Following the considerable interest in practice theory, this Collective Discussion interrogates what it means to practice and, ultimately, to think with diplomacy. In asking how empirical, methodological, and axiological disagreements over what constitutes diplomatic practice can be productively employed to develop or revise practice theory, the Discussion engages the historically and culturally contingent practices of diplomacy. In doing so, it goes beyond the conventional interactions that assume a fixed and singular identity for diplomacy. The Discussion aims, on the one hand, to pluralize the notion of diplomatic practice, and, on the other, to reflexively retrieve "theory" from the everyday and alternative practices of diplomacy that are often missed by the radar of practice theory. It thus seeks to reassess practice theory using insights from the very terrain of action it employs to develop its distinctive viewpoint. The Discussion contributes, moreover, to the rapidly changing field of Diplomatic Studies that has recently opened up to cross- and trans-disciplinary conversations with political geography, social anthropology, digital studies, visual studies, and new materialism.